2019
DOI: 10.1093/jpepsy/jsz019
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Maternal Mental Health: Longitudinal Trajectories and Predictors

Abstract: Objective To examine trajectories of psychological distress in mothers of children born very preterm (VPT, <30 weeks gestation) and full term from 2 to 13 years after the birth, and examine predictors of maternal psychological distress over time within the VPT group. Methods Mothers of children born VPT (n = 159) and full term (n = 71) completed questionnaires assessing their psychological distress when their child was 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 67 publications
2
47
0
1
Order By: Relevance
“…Besides, the period after preterm birth, including the physical environment of NICU and medical procedures, exacerbates adverse consequences of preterm birth on parental mental health (Treyvaud et al., 2011; Yaari, Treyvaud, Lee, Doyle, & Anderson, 2019). Specifically, parents of preterm infants were reported to have higher levels of stress and elevated rates of symptoms of depression and anxiety compared with parents of term‐born infants (Pace et al., 2016; Yaari et al., 2019), especially within the first year after preterm birth (Brummelte, Grunau, Synnes, Whitfield, & Petrie‐Thomas, 2011). Yet, there are also studies reporting a decrease in anxiety over time with decreasing health risks of a preterm infant (Schmücker et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the period after preterm birth, including the physical environment of NICU and medical procedures, exacerbates adverse consequences of preterm birth on parental mental health (Treyvaud et al., 2011; Yaari, Treyvaud, Lee, Doyle, & Anderson, 2019). Specifically, parents of preterm infants were reported to have higher levels of stress and elevated rates of symptoms of depression and anxiety compared with parents of term‐born infants (Pace et al., 2016; Yaari et al., 2019), especially within the first year after preterm birth (Brummelte, Grunau, Synnes, Whitfield, & Petrie‐Thomas, 2011). Yet, there are also studies reporting a decrease in anxiety over time with decreasing health risks of a preterm infant (Schmücker et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, infants with both prematurity and sociodemographic disadvantages were prone to have less optimal developmental outcomes compared to infants with prematurity alone (Candelaria, O'Connell, & Teti, 2006; Yaari et al., 2019). Several studies in the literature reported low socioeconomic status (SES; including parental education and income) as a risk factor for developing a secure mother–child attachment (Cyr, Euser, Bakermans‐Kranenburg, & van Ijzendoorn, 2010; De Falco et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 For women experiencing preterm birth, in addition to the negative emotional reactions mentioned above, they worried about the children's health and faced high parenting pressure. 18,19 Our study identi ed that women who encountered miscarriage or preterm birth because of TTTS would had more complex emotions. During pregnancy, in addition to surgery, they also dealt with the uctuation in foetal health, and their mood was calm only after a successful birth.…”
Section: Discussionmentioning
confidence: 99%
“…Women who experience fetal abnormalities, premature birth, or miscarriage may face post-traumatic stress, sadness, anxiety, and/or depression for a long time . 19,20 Women with TTTS have the disadvantages of premature births and miscarriage, and their pregnancy experiences are more complicated. A study indicated that the emotional reactions of whole family experiencing TTTS during pregnancy were like a roller coaster.…”
Section: Discussionmentioning
confidence: 99%